The Socialization of Capitalism through Social Enterprises - Jacek Brdulak; Ewelina lorczak; Tomasz Gardziński (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
The search for ways to develop capitalism and the ways of its socially acceptable configuration causes increasing attention of specialists. Recognizing the ways of overcoming economic stagnation in conditions of limited resources and the growing social awareness of increasingly better communicated networks of societies, encourages the formulation of ways to reform capitalism. Authors leave radical solutions beyond discussion, especially those known from history. The contemporary development of productive forces and socio-economic life creates new premises for changes in capitalist reality. The authors are especially interested in the pro-social character of this premise. To define the phenomenon of socialization of capital, the authors referred to the social market economy - a specific economic order, as well as to a social enterprise, i.e. an entity realizing social objectives as part of business operations. The social market economy and social enterprise have been indicated as an important element of the economy as well as the state's economic policy. To fulfill its goals and duties in the context of shaping the quality of life of the society, the state should include in the economic system market entities that fulfill socially useful goals as part of the market mechanism.